Berthe de Rayssac, muse et artiste sans œuvre - Sarah Hassid (Les Cahiers de l'École du Louvre)
An illustrator, musician and storyteller, Berthe de Rayssac (1846–1892) dabbled in various fields of creativity without really blossoming in any, nor beyond the confines of the salon that she hosted in the 1870s and 1880s. By retracing the career of this forgotten personality, notably through her artistic training and practice of music, it is possible to describe this ambivalent figure, who combined the symbolic faces of the muse and the artist, paradoxically without an oeuvre. Having renounced an artistic career from a very young age, Berthe de Rayssac did nevertheless play a crucial role in the cultural life of her time. Favouring an aestheticism of everyday life because she was unable to express herself fully in her works, she succeeded in making her small Parisian salon a cradle of symbolism entirely dedicated to the arts.